Makna Toponim Desa Durungbedug Sebeagi Representasi Warisan Budaya Lokal - Andi Fikri; Istiqomah Istiqomah; Arifin Mado (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to examine the meaning of toponyms in Durungbedug Village as a representation of local cultural heritage. Using a comparative historical linguistics approach, Barthes' etymology and semiotics, as well as ethnographic methods, this study explores the meaning of place names in the village. Scientific findings indicate that the toponyms of Durungbedug Village, consisting of Bedug Pesantren, Bedug Dowo, and Bedug Baru, reflect the existence of developing religious, agrarian, and economic values.